The Role of Silk in the Behaviour and Sociality of Spiders - Bertrand Krafft; Laurie J. Cookson (Psyche: A Journal of Entomology)
This article describes the links between the production of silk by spiders and their behaviour. Silk allows the spider to change its physical environment, which in turn leads to behavioural changes and impacts in the new environment. The feedback between silk and the animal producer can explain the architecture of spider webs and their adaptation to the environment, by referring only to stereotypic stimulus-response reactions without necessarily resorting to a “representation” by the animal of the structure it builds. Silk can act as a means of protection against environmental stress, a snare for prey, a means of locomotion, and also as support for chemical signals or to act as a vector of vibratory signals. These last two functions have undoubtedly played a key role in spider socialization and explains the phenomena of group cohesion, collective decision making, and the coordination of activities, without resorting to mental “representations” for the overall situation. The bulk of this review describes silk as the chief agent directing the construction of traps, communication, social cohesion, and cooperation amongst its producers.